Greed, grievances and anarchy at sea : human security and Somali piracy : a thesis presented in partial fulfillment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Rees, Aaron (Massey University, 2011)
In recent years there has been a dramatic upsurge in piracy off the Somali coast. In 2009 alone, there were 217 reported incidences of Somali piracy, with 857 seafarers being held hostage. This piracy clearly has significant ramifications for global security and development, and must therefore be addressed. It is often stated that piracy is little more than a ‘symptom’ of greater problems on land. However, current counter-‐piracy measures have largely been dominated by naval fixes, while failing to address the underlying issues driving piracy. This thesis adopts a human security framework to analyze the underlying economic, social, cultural, political and environmental conditions on land that are contributing to the causation of Somali piracy. This analysis is intended to evaluate economic rationalist (greed) and grievance-‐based understandings of piracy, and thus shed light on the root causes of Somali piracy, revealing possible avenues to address these causes. To achieve this aim, a qualitative analysis of media interviews with Somali pirates, and other key actors, has been conducted in combination with a critical review of available information on Somali piracy and human security in Somalia. Overall, this study finds that weak human security and external violations of human security in Somalia underpin many of the factors driving piracy off the Somali coast, suggesting that Somali piracy is a human security issue, which requires integrated development and security solutions. Therefore, this thesis proposes that ensuring human freedoms in Somalia is the only sustainable means of addressing Somali piracy.
Keywords: Hijacking of ships; Piracy; Maritime terrorism; Human security; Politics and government; Somalia; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science::Peace and development research